The near demise of Marlierea: moving last species to correct genera and notes on three incertae saedis taxa (Myrtaceae, Myrteae, Myrciinae) - Santos, Matheus F.; Stadnik, Aline; Proença, Carolyn E. B.; Sobral, Marcos (Phytotaxa, 2020)
Recent phylogenetic and taxonomic studies resulted in the synonymization of Marlierea into Myrcia. This paper aims to transfer the last Marlierea species to their correct genera, which include not only taxa belonging to Myrcia, but also to Eugenia, Plinia and Siphoneugena. Five new combinations are proposed: Eugenia choriophylla, based on Marlierea choriophylla; Myrcia resupinata, based on Myrtus resupinata; Plinia parvifolia, based on Marlierea parvifolia; Plinia sessiliflora, based on Marlierea sessiliflora; and Siphoneugena martinellii, based on Marlierea martinellii. Two new names are proposed: Myrcia rufopilosa, replacing Myrtus rufa; and Myrcia sintenisiana, replacing Marlierea sintenisii. A new synonym is proposed, Marlierea cordata under Eugenia hirta. Three names, Marlierea capitata, Marlierea involucrata and Marlierea occhionii remain as incertae saedis, and, additionally, we have listed two nomina nuda referenced in the literature as Marlierea.